Implementation of Muhadharah Activities in Training Students' Da'wah Abilities at MTs Negeri 4 Karawang - Ayuning Nurul Khasanah; Amirudin, Amirudin; Iqbal Amar Muzaki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The research aims to examine muhadharah activities at MTs Negeri 4 Karawang. To find out how the implementation process works and what are the supporting and inhibiting factors for its implementation. This research uses a qualitative approach with a case study method. Research data was obtained from observations, documentation and interviews. The research results show that the implementation of muhadharah activities involves various sequences such as opening, reading verses from the Koran and recitations, reciting dhikr, reciting prayers, and closing. MTs Negeri 4 Karawang demonstrated success by actively involving students in muhadharah activities with a task selection system. And the supporting factor is the availability of adequate facilities and infrastructure at MTs Negeri 4 Karawang, but the obstacle is the lack of enthusiasm of students and the absence of strict sanctions against students.